Women’s experiences of participation in mass participation sport events - Mirehie, Mona (Frontiers in Psychology, 2022)
Mass participation sport events (MPSEs) have become a popular form of recreational sport participation. Understanding experiences of participants is pivotal to designing and implementing socially just and sustainable events. Applying constructivist grounded theory methodology, this inquiry explored experiences of participation in MPSEs, with particular attention to the impact of gender on participation experiences. In-depth interviews were conducted with 13 women who participated in MPSEs. Fear and power were two core themes in interviewees’ experiences. Fear of sexual assault, injury, and “something bad” was a significant element in women’s experiences which related to perceptions of place and time. The second theme, power, was generated from strong sport identities, camaraderie among female runners, all-women races, and finishing mixed-gender races. The findings provide some guidelines for practitioners to enhance experiences of female participants and encourage repeated participation that is key to sustainability of the events.